Letter - Herrington, F.
034-0177-001 SOUTH ISLINGTON LABOUR PARTY (Affiliated to the National Labour Party and London Labour Party). President - - F. HERRINGTON Secretary: G. PARKER Treasurer: H.G. COLEMAN, J.P. Organising Com. Secretary: G.E. BLYTHE Women's Section Secretary: Mrs. HAMLET Vice-Presidents: Mrs J.L. BLYTHE & A.E. SMITH Premises Com. Secretary: C.E. COLEMAN Assistant Secretary: F. ROGERS Propaganda Secretary: League of Youth Secretary: F. DRAKE 295, UPPER STREET, N.1 Oct: 20th: 1937. Sir, I have been approached by one of our constituents re: her son who went to Spain. I wonder if you could put me on to someone who could he[l]p in tracing him. She has been informed that he was killed but naturally she wants to obtain some correct information. He went, I understand, 8 months ago. His name is James Wheeler, 11 Queens Cottages, Popham St. N.1. Trusting you can assist. F.J. Herrington 292/946/34/177